Mathematics in Artistic Design : Teaching Mathematics in Inventive Ways - Cashman, Roslyn; Hanson, Skyler; Bingen, Charles; Tong, Simei (My University, 2018)
Using our combined knowledge of mathematics, quilting, and artistic design, our research team created an inventive way of learning mathematics for those who may not share our enthusiasm for the subject. Together we created Mathematics in Artistic Design: a textbook about the unique ways that mathematics and artistic design intersect, specifically pertaining to quilting.
Color poster with text and images.
Keywords: Posters; Mathematics; Quilting; Artistic expression; Artistic design